Association Between Hospital Volume and Mortality in Status Epilepticus: A National Cohort Study. Issue 12 (December 2018) - Goulden, Robert; Whitehouse, Tony; Murphy, Nick; Hayton, Tom; Khan, Zahid; Snelson, Catherine; Bion, Julian; Veenith, Tonny
Abstract : Objectives: In various medical and surgical conditions, research has found that centers with higher patient volumes have better outcomes. This relationship has not previously been explored for status epilepticus. This study sought to examine whether centers that see higher volumes of patients with status epilepticus have lower in-hospital mortality than low-volume centers. Design: Cohort study, using 2010–2015 data from the nationwide Case Mix Programme database of the U.K.'s Intensive Care National Audit and Research Centre. Setting: Greater than 90% of ICUs in United Kingdom, Wales, and Northern Ireland. Patients: Twenty-thousand nine-hundred twenty-two adult critical care admissions with a primary or secondary diagnosis of status epilepticus or prolonged seizure. Interventions: Annual hospital status epilepticus admission volume. Measurements and Main Results: We used multiple logistic regression to evaluate the association between hospital annual status epilepticus admission volume and in-hospital mortality. Hospital volume was modeled as a nonlinear variable using restricted cubic splines, and generalized estimating equations with robust SEs were used to account for clustering by institution. There were 2, 462 in-hospital deaths (11.8%). There was no significant association between treatment volume and in-hospital mortality for status epilepticus ( p = 0.54). This conclusion was unchanged across a number of subgroup and sensitivity analyses, although we lacked data on seizure duration and medication use. Secondary analyses suggest that many high-risk patients were already transferred from low- to high-volume centers. Conclusions: We find no evidence that higher volume centers are associated with lower mortality in status epilepticus overall. It is likely that national guidelines and local pathways in the United Kingdom allow efficient patient transfer from smaller centers like district general hospitals to provide satisfactory patient care in status epilepticus. Future research using more granular data should explore this association for the subgroup of patients with refractory and superrefractory status epilepticus. Abstract : Supplemental Digital Content is available in the text.